A vanadium pentoxide / graphene composite material and its preparation method and application

By introducing metal magnesium ions and graphene into the vanadium pentoxide positive electrode material, the vanadium pentoxide/graphene composite material is solved, and the cathode material with high rate performance and long cycle stability of magnesium ion battery is achieved.

CN116314738BActive Publication Date: 2025-03-18CHONGQING UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310298952.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2025-03-18
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

Vanadium pentoxide positive electrode material has poor kinetic behavior in magnesium ion batteries. The strong interaction with Vanadium pentoxide during the magnesium ion embedding/deintercalation cycle leads to collapse of the matrix structure, resulting in rapid attenuation of capacity.

Method used

Vanadium pentoxide/graphene composite material is used to broaden the layer spacing by introducing metal magnesium ions between V2O5 layers, and using highly conductive graphene to enhance the dynamic behavior, forming a synergistic effect between interlayer pillars and highly conductive graphene, improving ion transport and electron conduction capabilities.

Benefits of technology

It significantly improves the storage efficiency of magnesium ions and the cyclic stability of the positive electrode material, achieves excellent rate performance and long cycle stability, and has a capacity retention rate of 87.3%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116314738B_ABST
    Figure CN116314738B_ABST
Patent Text Reader

Abstract

The invention discloses a vanadium pentoxide / graphene composite material and a preparation method and application thereof. The preparation steps include: dissolving vanadium pentoxide in a mixed solution of deionized water and hydrogen peroxide, adding a magnesium source and graphene in sequence, and then ultrasonicating to evenly disperse the graphene; then placing in an oven for hydrothermal reaction, cooling naturally, filtering, washing, drying and collecting to obtain a vanadium pentoxide / graphene composite material with metal magnesium ion intercalation. The invention adopts a simple one-step hydrothermal method to insert metal magnesium ions into layered V2O5, broadens the interlayer spacing of V2O5, and provides abundant active sites for magnesium ions. And the metal magnesium ions, as interlayer pillars, enhance the structural stability of the V2O5 matrix to support the reversible insertion / extraction of magnesium ions during the charge and discharge process. At the same time, the high-conductivity graphene nanosheets and V2O5 composite improve the ionic conductivity and electronic conductivity of the electrode material, and provide favorable kinetic conditions for the rapid extraction and insertion of magnesium ions in the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium battery positive electrode materials, and specifically relates to a vanadium pentoxide / graphene composite material and a preparation method and application thereof. Background Art

[0002] The rapid development of new energy storage systems has significantly alleviated the current energy crisis. Among them, energy storage devices based on metal lithium batteries have been fully developed and utilized due to their advantages such as high voltage, high energy density and long working time. However, the low safety, lithium dendrites and shortage of lithium resources in the charging and discharging process of lithium metal have prompted the rapid development of other metal ion batteries. Among them, the double charge transfer mechanism of magnesium ions has considerable theoretical specific capacity and excellent kinetic potential. In addition, magnesium resources are abundant, cost-effective and safe, making magnesium ion batteries occupy an important position in new energy storage systems. However, magnesium ions with double charges are lower than single-charged metal ions (Li + 、Na + , K + There is a stronger interaction between the positive electrode material and the host structure, which can easily cause the dissolution of the positive electrode material and the collapse of the host structure, resulting in rapid capacity decay. Therefore, there is an urgent need to find a positive electrode material with a stable crystal structure and a fast diffusion channel for magnesium ions to fully develop the electrochemical potential of magnesium batteries.

[0003] Vanadium pentoxide cathode materials are widely used in various metal ion batteries due to their high specific capacity, chemical valence state and diversity of crystal structure. For example, patent CN110078121A prepared vanadium pentoxide cathode materials by hydrothermal-calcination method and applied them to magnesium metal batteries. 2 BuEt) 2 / THF electrolyte system can reach an initial specific capacity of 120mAh / g, and the capacity retention rate is 70% after 60 cycles at a current density of 50mA / g. However, magnesium ions are easily complexed with anions in the electrolyte to make their ion radius much larger than the magnesium ions themselves, resulting in a large volume change of the host material during the charge and discharge process. After multiple cycles, it is easy to cause the dissolution of the vanadium pentoxide matrix and cause the specific capacity to decay rapidly. Therefore, it is necessary to modify the vanadium-based positive electrode material to improve the structural stability during the cycle. For example, patent CN114988471A discloses a method for modifying vanadium pentoxide electrode materials with cation pre-intercalation. By 2 O 5The introduction of cations between the layers to act as interlayer pillars greatly alleviates the structural degradation caused by the charge and discharge cycle. This ion pre-intercalation strategy improves the structural stability of the electrode material during the charge and discharge cycle to a certain extent. However, although the simple cation pre-intercalation strategy can reduce the volume change caused by the charge and discharge process to improve the long-cycle stability, the inherently poor ion transport and electron conduction capabilities of vanadium pentoxide still limit its application in magnesium ion batteries. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a vanadium pentoxide / graphene composite positive electrode material to solve the problems of poor kinetic behavior of vanadium pentoxide positive electrode material when used in magnesium ion batteries and the strong interaction between magnesium ion insertion / deinsertion cycle and vanadium pentoxide causing matrix structure collapse, resulting in rapid capacity decay.

[0005] Furthermore, a preparation method and application of the vanadium pentoxide / graphene composite material are provided.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0007] A vanadium pentoxide / graphene composite material, the microscopic morphology is a layered flake structure, and its chemical formula is Mg x V 2 O 5 / GO(0.01 <X<0.1),V 2 O 5 The interlayer spacing is 1.4 to 1.6 nm.

[0008] The vanadium pentoxide / graphene composite material of the present invention has a 2 O 5 The introduction of magnesium ions between the layers widens the V 2 O 5 The interlayer spacing is reduced to 1.45nm, providing abundant active sites for magnesium ions to improve the storage efficiency of magnesium ions. The interlayer magnesium ions act as "pillars", alleviating the volume changes caused by the charge and discharge process to improve long-cycle stability. At the same time, the highly conductive lamellar graphene oxide material enhances the kinetic behavior of vanadium pentoxide and shortens the migration path of magnesium ions to improve the rate performance of the positive electrode material. The synergistic effect of this interlayer pillar and highly conductive graphene greatly alleviates the problems of poor ion transmission and electron conduction of vanadium pentoxide electrodes, as well as structural stability during long cycles.

[0009] A method for preparing a vanadium pentoxide / graphene composite material comprises the following steps:

[0010] (1) dissolving vanadium pentoxide in deionized water, then adding hydrogen peroxide solution, and stirring until the vanadium pentoxide is completely dissolved;

[0011] (2) adding a magnesium source to the solution obtained in step (1) and stirring until completely dissolved;

[0012] (3) adding graphene to the solution obtained in step (2) and then sonicating;

[0013] (4) The solution obtained in step (3) is transferred into an oven for hydrothermal reaction, and then naturally cooled, filtered, washed, and dried to obtain a vanadium pentoxide / graphene composite material with a pre-intercalated magnesium ion layer.

[0014] Furthermore, the mass ratio of vanadium pentoxide to the magnesium source is 1:0.1-0.3.

[0015] Preferably, the mass ratio of vanadium pentoxide to magnesium source is 1:0.11-0.275.

[0016] Furthermore, the mass ratio of vanadium pentoxide to graphene is 1:0.8-2.5.

[0017] Preferably, the mass ratio of vanadium pentoxide to graphene is 1:1-2.

[0018] Furthermore, the reaction temperature of the hydrothermal reaction in step (4) is 100-200° C., and the reaction time is 1-3 h.

[0019] Furthermore, the magnesium source is one or more of magnesium nitrate hexahydrate, magnesium chloride, magnesium carbonate, and magnesium sulfate.

[0020] Furthermore, in step (4), the drying temperature is 60-100° C. and the drying time is 3-8 hours.

[0021] The vanadium pentoxide / graphene composite material prepared by the above method is used as a positive electrode material for a magnesium ion battery.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention adopts a simple one-step hydrothermal method to layered V 2 O 5 Inserting magnesium ions broadens the V 2 O 5 The interlayer spacing (1.45nm) provides abundant active sites for magnesium ions, thus improving the Mg x V 2 O 5 / GO cathode magnesium ion storage efficiency. And the metal magnesium ions as interlayer pillars enhance the V 2 O 5The matrix structure is stable to support the reversible insertion / extraction of magnesium ions during charge and discharge. At the same time, the highly conductive graphene nanomaterials improve the V 2 O 5 The high ionic and electronic conductivity is beneficial to the transport of magnesium ions and provides favorable kinetic conditions for the rapid embedding / de-embedding of magnesium ions in the matrix.

[0024] 2. Mg obtained by the present invention x V 2 O 5 When the / GO composite material is used as the positive electrode material of magnesium ion battery, the -1 The specific capacity is as high as 197.8 mAh g at the current density -1 ; Increase the current density to 3.0A·g -1 Time Mg x V 2 O 5 The specific capacity of the / GO cathode remains at 63.5 mAh g -1 ; at 0.5A·g -1 After 900 cycles at the current density, the capacity retention rate reached 87.3%, showing excellent rate performance and long-cycle stability. It is a highly potential high-rate performance and stable long-cycle magnesium ion battery positive electrode material. Its excellent rate performance is due to the presence of graphene, which significantly improves the conductivity of the composite electrode material, and enables more active sites to participate in electron gain and loss at high current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The present invention is a flow chart of the preparation process of the vanadium pentoxide / graphene composite material;

[0026] Figure 2 The Mg prepared by the present invention x V 2 O 5 / SEM image of GO;

[0027] Figure 3 Mg prepared by the present invention x V 2 O 5 / XRD pattern of GO;

[0028] Figure 4 Mg prepared by the present invention x V 2 O 5 Specific capacity diagram of / GO at different current densities;

[0029] Figure 5 The Mg prepared by the present invention x V 2 O5 Charge and discharge curves of / GO at different current densities;

[0030] Figure 6 The Mg prepared by the present invention x V 2 O 5 / GO at 0.5A·g -1 Long cycle test diagram under current density;

[0031] Figure 7 The Mg prepared by the present invention x V 2 O 5 / GO at 0.1mV s -1 Cyclic voltammetry curves at different scan rates;

[0032] Figure 8 The materials obtained in Example 1 and Comparative Examples 1-2 were tested at 1.0 mV s -1 Cyclic voltammetry curves at different scan rates. DETAILED DESCRIPTION

[0033] The specific implementation modes of the present invention are further described in detail below in conjunction with specific examples.

[0034] The numerical ranges in the present invention are understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any intermediate value in the stated value or stated range and any other stated value or intermediate value in the stated range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the range.

[0035] Unless otherwise stated, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art described in the present invention are generally understood. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of conflict with any incorporated document, the content of this specification shall prevail. Regarding "comprising", "including", "having", "containing", etc. used herein, they are all open terms, which means including but not limited to.

[0036] Unless otherwise specified, the experimental methods used in the present invention are all conventional methods.

[0037] Unless otherwise specified, the materials, reagents, etc. used in the present invention can be purchased or synthesized by known methods.

[0038] The quantitative tests in the present invention were all repeated three times, and the results were averaged.

[0039] See also Figure 1 The preparation process of the vanadium pentoxide / graphene composite material of the present invention comprises the following steps:

[0040] (1) dissolving vanadium pentoxide in deionized water, then adding hydrogen peroxide solution, and stirring until the vanadium pentoxide is completely dissolved;

[0041] (2) adding a magnesium source to the solution obtained in step (1) and stirring until completely dissolved;

[0042] (3) adding graphene to the solution obtained in step (2) and then sonicating;

[0043] (4) The solution obtained in step (3) is transferred into an oven for hydrothermal reaction, and then naturally cooled, filtered, washed, and dried to obtain a vanadium pentoxide / graphene composite material with a pre-intercalated magnesium ion layer.

[0044] Example 1

[0045] 0.182g V 2 O 5 Dissolve in 35 ml of deionized water, stir at room temperature, then add 10 ml of 30% H 2 O 2 Continuously stir at room temperature for 1 h until an orange-red transparent solution is formed. 3 ) 2 6H 2 O was added to the above orange-red transparent solution and stirred at room temperature for 1 h until Mg(NO 3 ) 2 6H 2 O was completely dissolved to obtain a uniform mixed solution. Then 12 ml of a 15 mg / ml graphene solution was added, and the graphene was evenly dispersed in the mixed solution at 80 W power for 2 h. The uniformly dispersed mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, heated to 200 ° C and kept warm for 2 h. After the reaction was completed, the oven was allowed to cool naturally. The obtained precipitated product was filtered and washed three times with deionized water, and then placed in a drying oven and dried at 80 ° C for 6 h to obtain Mg x V 2 O 5 / GO composites.

[0046] See also Figure 2 , is the Mg obtained in the present invention x V 2 O 5 SEM image of / GO, Figure 2 It is known that Mg x V 2 O 5 / GO presents a uniform flake structure, and graphene and vanadium pentoxide are uniformly composited to form a good conductive network to improve the kinetic behavior of the electrode.

[0047] See also Figure 3 , is the Mg prepared by the present invention x V 2 O 5 The XRD pattern of / GO is given by Figure 3 It is known that Mg x V 2 O 5 / GO has a typical layered structure with an interlayer distance of (1.45nm) has abundant active sites to improve the storage efficiency of magnesium ions.

[0048] See also Figure 4 , is the Mg prepared by the present invention x V 2 O 5 The charge and discharge diagram of the Mg / GO cathode at different current densities. x V 2 O 5 The / GO composite material was used as the positive electrode of magnesium ion battery for electrochemical performance test. -1 The specific capacity is as high as 197.8 mAh g at the current density -1 , increase the current density to 3.0A·g -1 Time Mg x V 2 O 5 The specific capacity of the / GO cathode remains at 63.5 mAh g -1 Mg prepared by the present invention x V 2 O 5 / GO material exhibits excellent rate performance when used as the positive electrode of magnesium ion batteries.

[0049] Figure 5 The Mg prepared by the present invention x V 2 O 5 / GO cathode at different current densities ( Figure 3 ) corresponding to the charge and discharge curve.

[0050] Figure 6 The Mg prepared by the present invention x V 2 O 5 / GO cathode at 0.5A·g -1 Long cycle test diagram under current density, by Figure 6 It is known that Mg x V 2 O 5 / GO cathode at 0.5A·g -1 The initial discharge capacity at the current density is 117.8 mAh g -1 After 900 charge and discharge cycles, the specific capacity is 102.8 mAh g -1 , the capacity retention rate reached 87.3%, showing that Mg x V 2 O 5 / GO cathode has excellent long-term cycle stability.

[0051] Figure 7 The Mg prepared by the present invention 0.07 V 2 O 5 / GO at 0.1mV s -1 The cyclic voltammetry curves of the first three cycles under the scanning rate are shown in Figure 2. Figure 7 It can be seen that in the first three cycles, the area and shape of the cyclic voltammetry curve did not change significantly, indicating that magnesium ions x V 2 O 5 / GO cathode can undergo reversible insertion / extraction cycles with good reversibility.

[0052] It can be seen that the Mg prepared by the present invention x V 2 O 5 When Mg / GO is used as the positive electrode material of magnesium ion batteries, Mg x V 2 O 5 / GO composite materials exhibit excellent rate performance and long-cycle stability, providing a direction for the research of high-rate performance and stable long-cycle magnesium-ion battery positive electrode materials.

[0053] Example 2

[0054] 0.182g V 2 O 5 Dissolve in 35 ml of deionized water, stir at room temperature, then add 10 ml of 30% H 2 O 2 Continuously stir at room temperature for 1 h until an orange-red transparent solution is formed. 3 ) 2 6H 2 O was added to the above orange-red transparent solution and stirred at room temperature for 1 h until Mg(NO 3 ) 2 6H 2O was completely dissolved to obtain a uniform mixed solution. Then 24 ml of a 15 mg / ml graphene solution was added, and the graphene was evenly dispersed in the mixed solution at 80 W power for 2 h. The uniformly dispersed mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, heated to 200 ° C and kept warm for 2 h. After the reaction was completed, the oven was allowed to cool naturally. The obtained precipitated product was filtered and washed three times with deionized water, and then placed in a drying oven and dried at 80 ° C for 6 h to obtain Mg x V 2 O 5 / GO composites.

[0055] Example 3

[0056] 0.182g V 2 O 5 Dissolve in 35 ml of deionized water, stir at room temperature, then add 10 ml of 30% H 2 O 2 Continuously stir at room temperature for 1 h until an orange-red transparent solution is formed. 2 6H 2 O was added to the above orange-red transparent solution and stirred at room temperature for 1 h until MgCl 2 6H 2 O was completely dissolved to obtain a uniform mixed solution. Then 12 ml of a 15 mg / ml graphene solution was added, and the graphene was evenly dispersed in the mixed solution at 80 W power for 2 h. The uniformly dispersed mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, heated to 200 ° C and kept warm for 2 h. After the reaction was completed, the oven was allowed to cool naturally. The obtained precipitated product was filtered and washed three times with deionized water, and then placed in a drying oven at 80 ° C for 6 h to obtain Mg x V 2 O 5 / GO composites.

[0057] Example 4

[0058] 0.182g V 2 O 5 Dissolve in 35 ml of deionized water, stir at room temperature, then add 10 ml of 30% H 2 O 2 Continuously stir at room temperature for 1 h until an orange-red transparent solution is formed. 3 Add to the above orange-red transparent solution and stir at room temperature for 1 h until MgCO 3Completely dissolve to obtain a mixed solution with uniform composition. Then add 12 ml of graphene solution with a concentration of 15 mg / ml, and ultrasonicate at 80 W power for 2 hours until the graphene is evenly dispersed in the above mixed solution. Transfer the evenly dispersed mixed solution to a stainless steel reactor with a polytetrafluoroethylene liner, heat it to 200 ° C and keep it warm for 2 hours. After the reaction is completed, wait for the oven to cool naturally. The obtained precipitated product is filtered and washed three times with deionized water, and placed in a drying oven at 100 ° C for 5 hours to obtain Mg x V 2 O 5 / GO composites.

[0059] Example 5

[0060] 0.182g V 2 O 5 Dissolve in 35 ml of deionized water, stir at room temperature, then add 10 ml of 30% H 2 O 2 Continuously stir at room temperature for 1 h until an orange-red transparent solution is formed. 0.03 g MgSO 4 Add to the above orange-red transparent solution and stir at room temperature for 1 h until MgSO 4 Completely dissolve to obtain a mixed solution with uniform composition. Then add 12 ml of graphene solution with a concentration of 15 mg / ml, and ultrasonicate at 80 W power for 2 hours until the graphene is evenly dispersed in the above mixed solution. Transfer the evenly dispersed mixed solution to a stainless steel reactor with a polytetrafluoroethylene liner, heat it to 200 ° C and keep it warm for 2 hours. After the reaction is completed, wait for the oven to cool naturally. The obtained precipitated product is filtered and washed three times with deionized water, and placed in a drying oven at 100 ° C for 5 hours to obtain Mg x V 2 O 5 / GO composites.

[0061] Table 1. Comparative table of raw material addition in examples

[0062]

[0063] Comparative Example 1

[0064] 0.182g V 2 O 5 Dissolve in 35 ml of deionized water, stir at room temperature, then add 10 ml of 30% H 2 O 2 , and continue stirring at room temperature for 1 hour until an orange-red transparent solution is formed. The uniform solution is transferred to a stainless steel reactor with a polytetrafluoroethylene liner, and the temperature is raised to 200°C and kept for 2 hours. After the reaction is completed, the oven is allowed to cool naturally. The obtained precipitate product is filtered and washed three times with deionized water, and then placed in a drying oven and dried at 80°C for 6 hours to obtain vanadium pentoxide material (V2 O 5 ).

[0065] Comparative Example 2

[0066] 0.182g V 2 O 5 Dissolve in 35 ml of deionized water, stir at room temperature, then add 10 ml of 30% H 2 O 2 Continuously stir at room temperature for 1 h until an orange-red transparent solution is formed. 3 ) 2 6H 2 O was added to the above orange-red transparent solution and stirred at room temperature for 1 h until Mg(NO 3 ) 2 6H 2 O was completely dissolved to obtain a mixed solution with uniform components. The uniform solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, heated to 200°C and kept warm for 2 hours. After the reaction was completed, the oven was allowed to cool naturally. The obtained precipitate was filtered and washed three times with deionized water, and then placed in a drying oven and dried at 80°C for 6 hours to obtain a vanadium pentoxide material (Mg x V 2 O 5 ).

[0067] Figure 8 The materials obtained in Example 1 and Comparative Examples 1-2 were tested at 1.0 mV s -1 Cyclic voltammetry curve at scan rate, V 2 O 5 Mg x V 2 O 5 and Mg x V 2 O 5 The cyclic voltammetry curve areas of the three materials / GO are shown in Table 2.

[0068] Table 2. V 2 O 5 Mg x V 2 O 5 and Mg x V 2 O 5 Comparison of cyclic voltammetry curve areas of three materials / GO

[0069] project <![CDATA[V 2 THE 5 ]]> <![CDATA[Mg x In 2 About 5 ]]> <![CDATA[Mg x V 2 O 5 / GO]]> Mathematical area of ​​cyclic voltammetry curve 0.000709 0.000828 0.001023

[0070] Depend on Figure 8 From Table 2, we can see that V 2 O 5 Mg xV 2 O 5 and Mg x V 2 O 5 The cyclic voltammetry curve areas of the / GO composite materials increase successively. It can be seen from formula (1) that:

[0071]

[0072] For the source of formula (1), see Mathis, TS; Kurra, N.; Wang,

[0073] The capacitance increases with the increase of the area of ​​the cyclic voltammetry curve, so the magnesium ion intercalation and graphene composite in the present invention can significantly improve the electrochemical performance of vanadium pentoxide. 2 O 5 Mg x V 2 O 5 Different degrees of polarization are shown in the CV curve, which reduces the migration rate of magnesium ions to a certain extent. x V 2 O 5 No polarization phenomenon was observed in the CV curve of / GO, indicating that the pre-intercalation and graphene composite electrode improved the magnesium ion migration efficiency, giving it good charge transfer kinetics and structural reversibility.

[0074] In summary, the present invention adopts a simple one-step hydrothermal method to layered V 2 O 5 Inserting magnesium ions broadens the V 2 O 5 The interlayer spacing (1.45nm) provides abundant active sites for magnesium ions, improving the storage efficiency of magnesium ions. And the metal magnesium ions act as interlayer pillars to enhance the V 2 O 5 The matrix structure is stable to support the reversible insertion / extraction of magnesium ions during the charge and discharge process. At the same time, the highly conductive graphene nanosheets and V 2 O 5 The compound improves V 2 O5 The synergistic effect of the strategy of pre-intercalation of magnesium ions and composite high-conductivity graphene provides favorable kinetic conditions for the rapid insertion / deintercalation of magnesium ions in the matrix.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.

Claims

1. A vanadium pentoxide / graphene composite material, characterized in that: The microscopic morphology is a layered flake structure with the chemical formula Mg x V2O5 / GO, where 0.01 < X < 0.1, the layer spacing of V2O5 is 1.4 - 1.6 nm, and metal magnesium ions are inserted into the layered V2O5; The preparation steps include: (1) Dissolve vanadium pentoxide in deionized water, then add hydrogen peroxide solution and stir until the vanadium pentoxide is completely dissolved; (2) adding a magnesium source to the solution obtained in step (1) and stirring until completely dissolved; (3) adding graphene to the solution obtained in step (2) and then dispersing it by ultrasonication; (4) The solution obtained in step (3) is transferred into an oven for hydrothermal reaction, and then naturally cooled, filtered, washed, and dried to obtain a vanadium pentoxide / graphene composite material with a pre-intercalated magnesium ion layer.

2. The vanadium pentoxide / graphene composite material according to claim 1, characterized in that: The mass ratio of vanadium pentoxide to magnesium source is 1:0.1-0.

3.

3. The vanadium pentoxide / graphene composite material according to claim 1, characterized in that: The mass ratio of vanadium pentoxide to magnesium source is 1:0.11-0.

275.

4. The vanadium pentoxide / graphene composite material according to claim 2 or 3, characterized in that: The mass ratio of vanadium pentoxide to graphene is 1:0.8-2.

5.

5. The vanadium pentoxide / graphene composite material according to claim 4, characterized in that: The mass ratio of vanadium pentoxide to graphene is 1:1-2.

6. The vanadium pentoxide / graphene composite material according to claim 1, characterized in that: The reaction temperature of the hydrothermal reaction in step (4) is 100-200° C., and the reaction time is 1-3 h.

7. The vanadium pentoxide / graphene composite material according to claim 1, characterized in that: The magnesium source is one or more of magnesium nitrate hexahydrate, magnesium chloride, magnesium carbonate and magnesium sulfate.

8. The vanadium pentoxide / graphene composite material according to claim 1, characterized in that: In the step (4), the drying temperature is 60-100° C. and the drying time is 3-8 hours.

9. Using the vanadium pentoxide / graphene composite material according to any one of claims 1 to 8 as a positive electrode material for a magnesium ion battery.

Citation Information

Patent Citations

  • Preparation method and application of vanadium pentoxide anode materials of magnesium ion batteries

    CN110078121A

  • Composite vanadium pentoxide-base material, preparation method thereof and use thereof

    CN109638257A

  • Vanadium pentoxide / graphene composite material and preparation method and application thereof

    CN109980205A